2018
DOI: 10.1101/482935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence that a major subpopulation of fall armyworm found in the Western Hemisphere is rare or absent in Africa, which may limit the range of crops at risk of infestation

Abstract: 2 1 Abstract 2 The introduction and establishment of fall armyworm (Spodoptera frugiperda) in Africa presents 3 a major threat to agriculture in that continent and potentially to the entire Eastern Hemisphere.4 The species is subdivided into two subpopulations called the R-strain and C-strain that differ in 5 their distribution on different plant hosts. This means that the scope of the economic risk posed 6 by invasive fall armyworm is influenced by whether one or both strains are present. Multiple 7 studies h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 46 publications
(35 reference statements)
1
15
0
Order By: Relevance
“…Further, we have analyzed individuals that appear to have a C-strain nuclear genome with an R-strain associated mitochondria (maternal lineage). This is consistent with the conflicting host strain assignments using specific genetic markers between R-strain and interstrain hybrids that was previously reported [22]. We still observe host differentiation at the nuclear genome level, though, and may suggest current single locus markers are not sufficient for surveying all S.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Further, we have analyzed individuals that appear to have a C-strain nuclear genome with an R-strain associated mitochondria (maternal lineage). This is consistent with the conflicting host strain assignments using specific genetic markers between R-strain and interstrain hybrids that was previously reported [22]. We still observe host differentiation at the nuclear genome level, though, and may suggest current single locus markers are not sufficient for surveying all S.…”
Section: Discussionsupporting
confidence: 90%
“…However, host preference is not absolute and discrepancies among haplotype markers have been reported. For example, the Tpi marker agrees with assortative mating and host assessments [22] in describing S. frugiperda samples from corn in the Eastern Hemisphere as Cstrain, yet a predominant COI-R strain marker is obtained in these collections [9]. These conflicting results may reflect interstrain hybridization [22] or be driven by maternally inherited symbionts that skew the distribution and diversity of certain haplotypes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Second, a methodology was developed that could detect suppression of interstrain mating in Western Hemisphere field populations by comparing the frequency of heterozygosity between strain-specific genetic polymorphisms with those that are nonspecific 38 . Application of this method to African fall armyworm found no evidence of similar strain-dependent mating behavior 39 . Third, previous studies in the Western Hemisphere indicate that approximately 20% of fall armyworm larvae collected from corn are of the R-strain based on a variety of molecular markers 17,21,25,40 , including TpiR (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Because of their hybridization, identification based on the maternally-inherited mitochondrial genotype is inaccurate and the insertion of two C-strain mitochondrial fragments in this study further confirms this inaccuracy. Therefore, it is not possible to accurately infer fall armyworm strain status based on the complete mitochondrial genome or the single COI mitochondrial gene, as suggested previously [40][41] . The Tpi gene, located in the nuclear genome, is more suitable for strain identification and 10 SNPs in this gene can distinguish between R-or C-strains fall armyworm in the Americas 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the molecular identification of the two strains of fall armyworm is dependent on which markers are used [35][36][37] . The early molecular markers based on mitochondrial Cytochrome Oxidase Subunit I (COI) and Z-chromosome-linked Triosephosphate isomerase (Tpi) genes failed to accurately assign strain identification [38][39][40][41] . The dominant population of fall armyworm invading Africa and Asia were speculated to be hybrid populations of the female R-strain and male C-strain, based on these two molecular markers 42 .…”
Section: Introductionmentioning
confidence: 99%